Benefits of the Mediterranean Diet in the Elderly Patient - Capurso, Antonio (Practical Issues in Geriatrics,, 2018)
This book illustrates the role of Mediterranean diet in connection with well-being and particularly its impact on health and elderly care, as well as on the mechanisms of aging. Aging is a natural process of human life. The knowledge that a healthy dietary regimen like the Mediterranean diet can effectively prevent or delay many diseases typically affecting aging people may help to better manage the aging process. From this point of view, knowledge of the numerous benefits of the Mediterranean-style diet may effectively promote better management of the burden of elderly care. As early as the 1950s, Ancel Keys pointed out the effectiveness of the Mediterranean diet in helping to control, and possibly avoid, myocardial infarction and/or cholesterol metabolism. Quite soon after the first studies were published, it became clear that the Mediterranean diet was beneficial not only in connection with cardiovascular disease but also many other diseases, from diabetes to hypertension, from cancer and thrombosis to neurodegenerative diseases, including dementia. Examining those benefits in detail, this book offers a valuable educational tool for young professionals and caregivers, as well as for students and trainees in Geriatrics and Nutrition.